Implementasi FMEA dan Perbaikan Tata Letak untuk Meningkatkan Produktivitas pada Departemen Dempul Painting di PT XYZ - Ayuningtyas, Virna Rahmadani; Arsiwi, Pramudi (Jurnal Teknik, 2025)
PT XYZ, a bus body manufacturing company, faces a high defect rate in the Putty and Painting Department, recording a total of 3,697 defects from January to October 2023, with the peak occurring in April at 521 cases (14.1%). The dominant defects include discoloration, overspray, waviness, and damage to the clear coat and putty, indicating a systemic issue. This study aims to identify major defects and determine improvement priorities using the Operation Process Chart, 8 Waste questionnaire, and Failure Mode and Effect Analysis (FMEA) based on the Risk Priority Number (RPN). Results show that the basecoat process has the highest RPN value of 80, while the baggage paint process has the lowest at 12. The main causes include overproduction, long workstation distances, excessive waiting time, unstable raw materials, lack of operator training, and weak inspection systems. Recommended improvements include SOP standardization, layout optimization, regular training, temperature and lighting control, and strengthening quality control to enhance product quality and production efficiency.